Adequacy of legal instruments for shaping the agricultural regime - Truszkiewicz, Zygmunt (Przegląd Prawa Rolnego, 2019)
The Act of 2003 on shaping the agricultural system was adopted following the concerns about potential acquisition of agricultural land by citizens from EU Member States. The same fears determined the tightening of restrictions on the ownership of agricultural land adopted in 2016. However, the effectiveness of these restrictions – from the point of view of the objectives articulated much more widely in the Act can hardly be noticed. The basic objective, which was to improve the area structure of agricultural holdings, has not really been achieved since during the 15 years of the operation of the Act, the State purchased only about 20 thousand hectares of agricultural land pursuant to its provisions. Further, the requirement underlying another objective of the Act (i.e. ensuring that agricultural activity is carried out in agricultural holdings by persons with appropriate qualifications) seems unreasonable in contemporary social and economic conditions and, what is more, it violates fundamental freedoms protected by the Constitution. Realistically, the Act has successfully albeit only partially achieved its third basic objective, which was to counteract excessive concentration of agricultural land, limiting the acquisition of agricultural land of an area exceeding 300 ha.